PENGARUH KOMPOSISI MALAM TAWON PADA PEMBUATAN BATIK KLOWONG TERHADAP KUALITAS HASIL PEMBATIKAN - Abdul Malik; Retno Retno; Ayu Ayu (Teknoin, 2016)
Batik is a visual art that integral to the cultural identity as well as illustrates the life values upon which the life of community is laid. It uses a technique of wax resist dyeing applied to whole cloth. This research aims to know the composition of beeswax that required on batik klowong and to know its effect to the results. The research used both qualitative and quantitative methods such as ingredients measurement technique, questionnaire distribution and voters calculation. The wax for batik klowong consist of beeswax, resin, and white paraffin. The beeswax is an independent variable that is varied in the composition for five different sample (10 gram, 20gram, 30gram, 40gram , 50gram). The sharpnesss of the motifs is visually analysed by six respondents. The results showed that sample D and E have better quality than the other samples. While sample A has the highest level of motifs sharpness.